2019
DOI: 10.1017/s1355617719000353
|View full text |Cite
|
Sign up to set email alerts
|

Medial Temporal Lobe Atrophy is Related to Learning Strategy Changes in Amnestic Mild Cognitive Impairment

Abstract: Objective: Deficits in the semantic learning strategy were observed in subjects with amnestic mild cognitive impairment (aMCI) in our previous study. In the present study, we explored the contributions of executive function and brain structure changes to the decline in the semantic learning strategy in aMCI. Methods: A neuropsychological battery was used to test memory and executive function in 96 aMCI subjects and 90 age- and gender-matched healthy controls (HCs). The semantic clustering ratio on the verbal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 73 publications
2
14
1
Order By: Relevance
“…The differences in cognitive function, such as memory, executive function, and information processing speed, between patients with amnestic mild cognitive impairment (aMCI) and patients with vascular cognitive impairment‐no dementia, who are considered as subjects with potentially prodromal stages for AD and VaD, respectively, were demonstrated in our previous study 17 . Moreover, we also found obvious impairment in the semantic learning strategy, which was attributable to MTA but independent of executive dysfunction and subcortical WMH in patients with aMCI 18 . In the present study, we aimed to establish the neuropsychological characteristics of SIVD patients and to find an optimal cognitive marker for differentiating mild to moderate patients with SIVD and AD.…”
Section: Introductionsupporting
confidence: 59%
“…The differences in cognitive function, such as memory, executive function, and information processing speed, between patients with amnestic mild cognitive impairment (aMCI) and patients with vascular cognitive impairment‐no dementia, who are considered as subjects with potentially prodromal stages for AD and VaD, respectively, were demonstrated in our previous study 17 . Moreover, we also found obvious impairment in the semantic learning strategy, which was attributable to MTA but independent of executive dysfunction and subcortical WMH in patients with aMCI 18 . In the present study, we aimed to establish the neuropsychological characteristics of SIVD patients and to find an optimal cognitive marker for differentiating mild to moderate patients with SIVD and AD.…”
Section: Introductionsupporting
confidence: 59%
“…For instance, apart from learning, delayed recall, and recognition, semantic clustering ratio was also found to be decreased during learning and memory process in subjects with aMCI compared with healthy individuals and subjects with vascular cognitive impairment-no dementia in our previous study (Sun et al, 2016). Our group further revealed that the impaired semantic learning strategy of aMCI was attributable to medial temporal lobe atrophy, which is the early pathologically involved brain area in patients with AD (Zhang et al, 2019).…”
supporting
confidence: 54%
“…SemC refers to a phenomenon by which individuals reorganize items based on a shared semantic feature and then consecutively recall the words based on their superordinate category during the recall process (Becker and Lim, 2003). We have previously observed that SemC was decreased in a learning and memory assessment in persons with amnestic mild cognitive impairment and further revealed that this decline was attributable to medial temporal lobe atrophy (Zhang et al, 2019), indicating that semantic learning strategies play an important role in episodic memory and could be a potential marker for the early diagnosis of AD. In addition to the medial temporal lobe, the prefrontal cortex has been suggested to be involved in the process of semantic clustering during coding and recall.…”
Section: Discussionmentioning
confidence: 99%